Nanosilver inhibits nitrification and reduces ammonia‐oxidising bacterial but not archaeal amoA gene abundance in estuarine sediments. (29th July 2016) - Beddow, Jessica; Stolpe, Björn; Cole, Paula A.; Lead, Jamie R.; Sapp, Melanie; Lyons, Brett P.; Colbeck, Ian; Whitby, Corinne
Summary: Silver nanoparticles (AgNPs) enter estuaries via wastewater treatment effluents, where they can inhibit microorganisms, because of their antimicrobial properties. Ammonia‐oxidising bacteria (AOB) and archaea (AOA) are involved in the first step of nitrification and are important to ecosystem function, especially where effluent discharge results in high nitrogen inputs. Here, we investigated the effect of a pulse addition of AgNPs on AOB and AOA ammonia monooxygenase ( amoA ) gene abundances and benthic nitrification potential rates (NPR) in low‐salinity and mesohaline estuarine sediments. Whilst exposure to 0.5 mg L −1 AgNPs had no significant effect on amoA gene abundances or NPR, 50 mg L −1 AgNPs significantly decreased AOB amoA gene abundance (up to 76% over 14 days), and significantly decreased NPR by 20‐fold in low‐salinity sediments and by twofold in mesohaline sediments, after one day. AgNP behaviour differed between sites, whereby greater aggregation occurred in mesohaline waters (possibly due to higher salinity), which may have reduced toxicity. In conclusion, AgNPs have the potential to reduce ammonia oxidation in estuarine sediments, particularly where AgNPs accumulate over time and reach high concentrations. This could lead to long‐term risks to nitrification, especially in polyhaline estuaries where ammonia‐oxidation is largely driven by AOB.